STUDENTS’ PERSPECTIVE TOWARD NATIONAL EXAMINATION IN INDONESIA - Ratnasari, Weni (Program Studi Ekonomi Syariah STAI Auliaurrasyidin Tembilahan, 2018)
National exam is one of big issues in IndonesianEducational system. Major controversies occur inimplementing the national examination. As a statemandatory exam that every student has to participate, itdetermines whether a student deserves to graduate or muststay. The policy makers believe if such condition isapplied, teachers will be pushed to teach better andstudents will be motivated to learn more. However, someresearch revealed negative impacts along the release ofsuch policy. It sparks negative impacts that policy makersshould be aware. This article discusses students?perspective regarding the benefits and drawbacks ofNational exam, and solution for better implementation ofNational Examination in Indonesia. Keywords: National Exam, Educational System.